Flotatión and recovery of fluorite of a polysulfhide ore of seal with lead-silver-zinc-iron - Azañero Ortiz, Ángel (2006)
Fluorite (F2Ca) is an ore that has multiple aplications, the main ones are: manufacture of fluorhidric acid, steel iron industry, welding and ornamental purposes. This ore belongs to the central zone of Peru and besides fluorite, it has metallic values of lead, silver and zinc, these respond well to differential flotation of sulfhur with good results in the quality of the concentrates and high recoveries. The obtained fluorite concentrate is of ceramic degree, fluorite of acid degree ca not be obtained because of the presence of Aluminium fluorides that affect the quality of the concentrate.